2013
DOI: 10.5798/diclemedj.0921.2013.04.0345
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of anterior segment parameters with pentacam according to age in emmetropic eyes

Abstract: Objective: It was aimed to compare anterior segment parameters obtained by rotating Scheimpflug camera system according to age groups.Methods: 290 eyes of 145 emmetropic subjects were included in the study. Subjects were divided in three age groups. Group 1 comprised the subjects age up to 20 years, Group 2 comprised the subjects age between 21 and 40 and Group 3 comprised the subjects between 41 years and older. In all subjects, flat keratometry (K1), steep keratometry (K2), mean corneal power (Km), maximum k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
1
1
Order By: Relevance
“…In some studies, CCT has been shown to decrease with increasing age [20,21], while in others, it was unrelated [19]. In a study conducted in our country, it was stated that CCT increased in older age groups [22]. In our study, no significant relationship was found between CCT and age.…”
Section: Discussioncontrasting
confidence: 63%
“…In some studies, CCT has been shown to decrease with increasing age [20,21], while in others, it was unrelated [19]. In a study conducted in our country, it was stated that CCT increased in older age groups [22]. In our study, no significant relationship was found between CCT and age.…”
Section: Discussioncontrasting
confidence: 63%
“…1,2 Current devices for measuring posterior corneal analysis use scanning-slit corneal topography (Orbscan; Bausch & Lomb, Inc.), color light-emitting diode topography (Cassini system; i-Optics Corp.; Ophtec), swept-source optical coherence tomography (SS-OCT), and Scheimpflug imaging. [3][4][5][6][7][8][9][10] IOLMaster 700, Anterion (Heidelberg Engineering GmbH), and Eyestar 900 (Haag-Streit AG) devices are based on SS-OCT technology. The Scheimpflug imaging technique is available in many devices such as the Pentacam HR, the Sirius (Costruzione Strumenti Oftalmici), the TMS-5 (Tomey Corp.), and the Galilei (Ziemer Ophthalmic Systems AG).…”
mentioning
confidence: 99%